Comparative evaluation on the masking ability of different tooth colored restoration over blackish discoloration caused by 38% silver diamine fluoride: an in -vitro study - Prajval Mahajan; Anupama Nayak P; Srikant Natarajan; Karuna Yarmunje Mahabala; Kiran N Baliga; Ashwin Rao; Charisma Thimmaiah (BDJ Open)
Abstract Background The application of Silver diamine fluoride is an effective approach in controlling dental caries. But the black discoloration caused by its application is unaesthetic and is of greater concern to the parents. Aim To assess the potential color masking ability of tooth colored restorative material over discoloration caused by 38% SDF using a UV‒VIS-NIR spectrophotometer. Material and methods 20 extracted teeth were taken and randomly divided into 4 groups: Group A: 38% SDF + GIC; Group B: 38% SDF + RMGIC; Group C: 38% SDF+ Composite; Group D: 38% SDF+ Cention N. Two readings were recorded, one on application of 38% SDF and second after application of test materials using a UV‒VIS-NIR spectrophotometer. Result The intragroup comparison for color masking ability (ΔE) for all four restorative materials revealed no statistically significant differences, with a test value of 1.168 and a p value of 0.353, and the highest mean was observed in Group A, i.e., 38% SDF + GIC (9.171966) Significant differences in color were observed, with more shifts toward yellow in group A (2.488 ± 2.957) and group D (1.686 ± 0.559) and more shifts toward green in groups B (−0.088 ± 0.34) and C (−0.062 ± 0.5). The mean lightness was greatest for Group C, i.e., the composite group (86.396 ± 3.741), and least for Group A, i.e., the GIC group (76.664 ± 8.213). Conclusion All 4 restorative materials were equally effective in terms of color masking over 38% SDF discoloration.